Quality performance evaluation of thin walled PLA 3D printed parts using the taguchi method and grey relational analysis - Aslani, Kyriaki-Evangelia; Chaidas, Dimitrios; Kechagias, John; Kyratsis, Panagiotis; Salonitis, Konstantinos (MDPI, 2020)
This paper investigates the quality performance of FDM 3D printed models with thin walls. The design of experiments method (DOE) was used and nine models of the same size were fabricated in a low-cost 3D printer using polylactic acid (PLA) material. Two limited studied parameters were considered (extraction temperature and wall thickness), each one having three levels. External X and Y dimensions were measured using a micrometer, as well as four surface roughness parameters (Ra, Rz, Rt, Rsm) with a surface tester. Two optimization techniques (the Taguchi approach and Grey relational analysis) were utilized along with statistical analysis to examine how the temperature and wall thickness affect the dimensional accuracy and the surface quality of the parts. The results showed that high extraction temperature and median wall thickness values optimize both dimensional accuracy and surface roughness, while temperature is the most important factor.
Keywords: grey relational analysis; Taguchi approach; surface roughness; dimensional accuracy; wall thickness; extraction temperature; optimization; PLA; FDM; additive manufacturing